Nomograms for prediction of breast cancer in breast imaging reporting and data system (BI-RADS) ultrasound category 4 or 5 lesions: A single-center retrospective study based on radiomics features - Hong, Zhi-Liang; Chen, Sheng; Peng, Xiao-Rui; Li, Jian-Wei; Yang, Jian-Chuan; Wu, Song-Song (Frontiers in Oncology, 2022)
Purpose: To develop nomograms for predicting breast cancer in BI-RADS ultrasound(US) category 4 or 5 lesions based on radiomics features. Methods: Between January 2020 and January 2022, we prospectively collected and retrospectively analyzed the medical records of 496 patients pathologically proven breast lesions in our hospital.The data set was divided into model development group and validation testing group with a 75/25 split. Radiomics features were obtained using the PyRadiomics package, and the radiomics score was established by least absolute shrinkage and selection operator regression. A nomogram was developed for BI-RADS US category 4 or 5 lesions based on the results of multivariate regression analysis from the training group. Result: The AUCs of radiomics score consisting of 31 US features was 0.886. The AUC of the model constructed with radiomics score, patient age ,lesion diameter identified by US and BI-RADS category involved was 0.956 (95% CI, 0.910–0.972) for the training cohort and 0.937 (95% CI, 0.893–0.965) for the validation cohort. The calibration curves showed good agreement between the predictions and observations. Conclusions: Both nomogram and radiomics score can be used as tools to assist clinicians in predicting breast malignancy in BI-RADS US category 4 or 5 lesions.